Blastocyst production after intracytoplasmic sperm injection with semen from a stallion with testicular degeneration. (1st March 2018) - Roels, K; Smits, K; Ververs, C; Govaere, J; D'Herde, K; Van Soom, A
Contents: In horse breeding, intracytoplasmic sperm injection (ICSI) has gained interest to obtain offspring from subfertile individuals. This paper presents a case report of a stallion with severe testicular degeneration. Semen analysis showed very low motility and 83.5% of detached heads. Histology of a testicular biopsy showed severely decreased spermatogenesis, while transmission electron microscopy of the sperm cells revealed no significant abnormalities. A total of 39 oocytes were fertilized by ICSI with frozen‐thawed spermatozoa of this stallion: 25 oocytes with intact spermatozoa and 24 with detached heads. When using intact sperm cells, 8 out of the 25 oocytes cleaved, and 1 developed to the blastocyst stage 9 days after ICSI. None of the oocytes injected with a detached sperm head cleaved. Studies on the paternal influence on ICSI outcome are limited in the horse and further research is needed to define which stallion factors may influence ICSI results. Here, we report the possibility to produce a blastocyst by ICSI of a stallion suffering from testicular degeneration with a poor spermiogram, as long as an intact sperm cell containing a centriole is selected.